THE CULTURAL AND EDUCATIONAL VIEWS OF ABDIKADIR BEKIMBET UGLI - Seytmuratov, Qalbay (SCIENCE and SOCIETY, 2026)
The state is considering the cultural and educational views of the talented poet Abdukadir Bekimbet oglu, a martyr and enlightened son of the Karakalpak people.
Keywords: culture; education; enlightenment; school; madrasah; literature; Jadidism; textbook.